Revisiting the deformed high shoreline of Lake Bonneville. (1st March 2017) - Chen, Christine Y.; Maloof, Adam C.
Abstract: Since G. K. Gilbert's foundational work in the eastern Great Basin during the late 1800s, the late Pleistocene Lake Bonneville (30–10 ka) has been recognized as a natural laboratory for various Quaternary studies, including lithospheric deformation due to surface loading and climate-forced water balance changes. Such studies rely on knowledge of the elevations of Lake Bonneville's paleoshoreline features and depositional landforms, which record a complex history of lake level variations induced by deglacial climate change. In this paper, we present (1) a new compilation of 178 elevation measurements of shoreline features marking Lake Bonneville's greatest areal extent measured using high-precision differential GPS (dGPS), and (2) a reconstructed outline of the highest shoreline based on dGPS measurements, submeter-resolution aerial imagery, topographic digital elevation models (DEMs), and field observations. We also (3) devise a simplified classification scheme and method for standardizing shoreline elevation measurement for different shoreline morphologies that includes constraints on the position of the still water level (SWL) relative to each feature type. The deformation pattern described by these shoreline features can help resolve the relative effects of local hydro-isostasy due to the lake load and regional solid earth deflection due to the Laurentide ice sheet, with potential implications for Earth rheology, glacial isostatic adjustment, and eustatic sea level change. Graphical abstract: Highlights: A new dataset of elevation measurements of Bonneville shoreline features using high-precision differential GPS. The location of shoreline features is improved by 3 orders of magnitude compared to dataset by Currey (1982). Quantification of uncertainties on position of still water level relative to shoreline feature elevation measurements. A classification scheme and method for standardizing shoreline elevation measurement applicable to any shoreline-related study in the world. A reconstructed outline of the Bonneville shoreline based on field observations, dGPS measurements, and satellite imagery.